A novel hybrid free-wake model for wind turbine performance and wake evolution. (February 2019) - Su, Keye; Bliss, Donald
Abstract: A new free-wake analysis for wind turbine aerodynamics is developed to accurately predict turbine performance and downstream wake evolution. A key feature is the Constant Circulation Contour Method (CCCM) which is a novel free-wake model for wind turbine wakes. This method characterizes a turbine wake by a number of resultant vortex filaments, avoiding the numeric artifact of a vortex lattice comprised of trailing and shedding vortices. The natural capture of wake roll-up and distortion using CCCM is illustrated and its computational complexity is demonstrated to be lower than Vortex Lattice Method (VLM). For accurate blade downwash calculation, a hybrid free-wake model is developed by combining CCCM with a VLM wake immediately behind turbine blades, which transitions to CCCM further downstream. Important properties of this hybrid wake are discussed and optimized to enhance model accuracy and efficiency. Blade static stall and unsteady effects are included. The hybrid model is validated through comparison to the wind tunnel experiments UAE Phase VI and MEXICO. Simulation examples are presented showing the utilization of this free-wake analysis to investigate wake steering, demonstrating the potential application of this method to wind farm scale wake simulations. Highlights: A novel free-wake model, Constant Circulation Contour Method (CCCM), is proposed. CCCM efficiently predicts turbine wake evolution using resultant vortices. A blade and near-wake Vortex Lattice Method includes stall and unsteady effects. Validation with experiments shows excellent loads and flow velocity agreement. Applicable to performance prediction, wake steering and wake shielding reduction.